P. BnF 239: A Demotic Wine Account on the Recto of a Document of Breathing - Dogaer, Lauren (Zeitschrift für ägyptische Sprache und Altertumskunde, 2025)
This paper examines the Demotic text of P. BnF 239, which is held in the Bibliothèque Nationale de France in Paris. The text, written in the 2 nd Century CE, contains several lists of wine deliveries that were likely brought to a temple in Thebes as payments in kind. The verso of the papyrus was reused for a Hieratic version of a Document of Breathing, a funerary composition that is typical of the Theban area.